The hidden history of Burma : race, capitalism, and the crisis of democracy in the 21st century - Thant Myint-U (W. W. Norton & Company, Inc., 2019)
"How did one of the world's "buzzy hotspots" (Fodor's 2013) become one of the top ten places to avoid (Fodor's 2018)? Less than a decade ago, the world cheered as a dictatorship crumbled and internationally beloved Nobel Laureate Aung San Suu Kyi emerged from twenty years of house arrest. Yet just three years after her landslide victory at the polls, the country stands accused of war crimes and the expulsion of hundreds of thousands of Rohingya Muslims. As an historian, former diplomat, and presidential advisor, Thant Myint-U was part of the momentous changes that pulled Burma toward democracy, working with the ex-generals and meeting many of the country's biggest supporters, from Bono to Barack Obama. Yet no one was prepared to Burma's underlying challenges, from fast- rising inequality, disintegrating state institutions, and the impacts of climate change, to the rise of China next door and the issues of race, religion, and "national identity" deeply rooted in the country's traumatic colonial past. In this riveting insider's diagnosis of a country at a breaking point, Thant Myint-U shows that Burma's perils, far from being unique, are many of the same facing all of us. Burma is a warning for the world"--